Financial Performance Analysis at PT. Borneo Olah Sarana Sukses Tbk (BOSS) Periode 2016-2020 - Dwi Budi Srisulistiowati; Rani Suryani (East Asian Journal of Multidisciplinary Research, 2022)
Analyzing financial ratios helps determine whether a company's financial performance is good or not. This study aims to evaluate the financial performance of PT. Borneo Olah Sarana Sukses Tbk (BOSS) uses the ratio analysis of profitability, solvency, liquidity, and activity. The data used are financial reports for the years 2016 – 2020. This research is a comparative descriptive study by examining annual financial statements, and using financial ratio analysis. Based on the profitability ratio of PT. Borneo Olah Sarana Sukses Tbk (BOSS) is in the unprofitable category although the return on equity ratio is  excellent  condition, based on the liquidity ratio in the illiquid category, the solvency ratio in the non-solvable category, and the activity ratio in the poor category. So, it can be concluded that the financial performance of PT. Borneo Olah Sarana Sukses Tbk (BOSS) is in the poor category.